1972
DOI: 10.1139/z72-188
|View full text |Cite
|
Sign up to set email alerts
|

The Cladocera of Ontario with remarks on some species and distribution

Abstract: The Cladocera of Ontario were studied from material collected over a wide geographical area. In all 244 lakes and 33 ponds were sampled, some of them more than once.A method for making stained permanent preparations of Cladocera used in our study is described.The genus Daphnia is richly represented. Based on a study of this material we have raised Daphnia pulicaria Forbes from synonymy in the North American fauna. The common limnetic species have been demarcated more satisfactorily. A hitherto undescribed Daph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 137 publications
(72 citation statements)
references
References 12 publications
4
68
0
Order By: Relevance
“…This result was not unexpected, as prior taxonomic studies established the presence of D. pulicaria in western ponds (Brooks, 1957;Brandlova et al, 1972). The present study has made it clear that F1 hybrids between D. pulex and D. pulicaria are common at sites across Canada and reproduce asexually.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This result was not unexpected, as prior taxonomic studies established the presence of D. pulicaria in western ponds (Brooks, 1957;Brandlova et al, 1972). The present study has made it clear that F1 hybrids between D. pulex and D. pulicaria are common at sites across Canada and reproduce asexually.…”
Section: Discussionsupporting
confidence: 80%
“…A posteriori morphological studies on each population confirmed that individuals assigned to D. pulex and D. pulicaria showed the divergence in head shape characteristic of these species (Brooks, 1957;Brandlova et at., 1972). To assess the genotypic structure of each population, 44 individuals were scored for allozyme variation at six additional loci (Ao, Fum, Got, Mpi, Pgi, Pgm), which (4) Jasper (5), Blue Ridge (6), Red Deer (7), Medicine Hat (8), Provost (9) Prince Albert (10), Moose Jaw (11), Jan Lake (12) Russell (13) (27) Moncton (28) Yarmouth (29), Sherbrooke (30), Igonish Beach (31) Cavendish (32) are commonly polymorphic.…”
Section: Introductionmentioning
confidence: 82%
“…Numerous studies have outlined physiological and life history differences between North American D. pulex and D. pulicaria (e.g., Brandlova et al 1972;Tessier and Consolatti 1991;Dudycha 2004;Weider et al 2004). In some parts of their distribution, D. pulex and D. pulicaria switch to sexual reproduction in response to different photoperiodic cues, resulting in a prereproductive isolating barrier (Deng 1997), and they usually occupy different but geographically overlapping habitats.…”
Section: Resultsmentioning
confidence: 99%
“…Because multilake studies (e.g. Brandlova et al 1972) have shown that phenotypic variation is much greater among lakes than within lakes, prior allozyme studies have examined only a small fraction of the total morphological variation in the species. Furthermore, the probability of detecting an association between genotype and phenotype increases with the number of allozyme marker loci used.…”
mentioning
confidence: 99%
“…Morph 2's possession of a cephalic crest and its occupancy of lakes in the eastern half of North America provided Brooks (19573) with the justification for its fusion with D. galeata mendotae. However, it is now well known that D. rosea occurs throughout most of North America (Brandlova et al 1972). Moreover, Brooks (1957b) acknowledged that "robust" forms of D. Germany (Wolf and Mort 1986) and 1.3% of the complex in Czechoslovakia (Hebert et al 19893).…”
mentioning
confidence: 99%